Teachers’ Perceptions towards the Content of Secondary School Islamic Studies Curriculum in relation to Vocational Islamic Education Values in UAE - Ibrahim, Anwar (2016)
Moral education is a fundamental component of Islamic Studies Curriculum therefore, Islamic values in relation to Vocational and Technical Education are best taught through Islamic Studies. This is an integrated way of education that encompasses all aspects of life including Vocational and Technical fields. The main purpose of this study is to investigate the teachers’ views towards including Islamic values in the educational textbooks taught in vocational and technical schools in the United Arab Emirates. The study comprises the participation of 56 Islamic Studies teachers, nine lead teachers and two curriculum specialists from vocational and technical schools, centers and institutes in the UAE. Multiple instruments were employed in a mixed methods approach to collect sufficient data for the study. A questionnaire with close and open-ended questions was used to report the teachers’ perceptions. Interviews were conducted from lead teachers and curriculum specialists. Interviews were conducted to collect data to lead teachers and curriculum specialists. This is in addition to analyzing contents of the prescribed Islamic Studies textbooks relevant to grade 10. The significant outcome indicated that age group is one of the main determinants of value allocation within the Islamic Studies curriculum. Islamic values existed in the Islamic Studies textbooks throughout the curriculum from G1 through G12. However, Grade 10 Islamic Studies textbooks lacked these values in comparison to the actual teachings in Islam. Therefore, the study recommends a fair distribution and reinforcement of values across the Islamic curriculum by developing a new curriculum that incorporates morals and values. In addition, curriculum training sessions for teachers are necessary to derive maximum values and Islamic principles.